Strategi Meningkatkan Kepuasan Karyawan AirNav Indonesia Cabang Semarang melalui Pengelolaan Digital Overload dan Komitmen Organisasi Sebagai Mediasi - Afrillya Margaretha Mangkawa; Awanis Linati Haziroh; Aris Puji Purwatiningsih; Tito Aditya Perdana (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to investigate how digital overload affects employee job satisfaction at AirNav Indonesia Semarang Branch, with organizational commitment as a mediating factor and organizational culture as a reinforcing element. The approach used was quantitative with a causal design. The study involved 62 employees through a saturated sampling technique, and data were collected through a questionnaire with a five-level Likert scale. Analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The main findings indicate that digital overload has an insignificant negative impact on job satisfaction. However, digital overload significantly affects organizational commitment in a negative direction. On the other hand, organizational commitment is proven to have a significant positive influence on job satisfaction. Further analysis revealed that organizational commitment significantly mediates the relationship between digital overload and job satisfaction. Organizational culture, on the other hand, does not show a significant influence on job satisfaction, nor does it function as a mediator or moderator. Overall, these results emphasize that the effect of digital overload on job satisfaction is stronger through changes in employee work attitudes, especially in terms of organizational commitment.